Usability of Online Banking in India during Covid-19 Pandemic - Mayank Jindal; Dr. Vijay Laxmi Sharma (International Journal of Engineering and Management Research, 2020)
Covid-19 is a virus developed in 2019 from the corona family virus. It is spreading across the world since Dec 2019 by the close contact of an infected person or fomites of Covid-19. It developed naturally in Wuhan (An State of China) or possibly develop by China research center “Wuhan Institute of Virology”. It is spreading very fast across the world. World Health Organization and most countries including India it has declared a pandemic. People can protect themselves by this pandemic by maintaining social distance. But the basic need (Food and Medicine) is important for continuo their life and in it the transfer of money plays an important role. Online banking can make the transaction through an electronic basis without the exchange of any tangible commodity with maintaining social distance. Online banking is the modern concept of banking in which people can do some banking activities (like Transfer cash transfer and in the account, Check Bank Balance, Payment of Bills, Phone recharge and etc.) through using the Internet in their phone, computer. One of the most important features of online banking is that it can totally operate electronically basis without the exchange of any tangible commodity and it has made it an important tool to protect from the pandemic. The purpose of this study is to assess the contribution of online banking to stop the pandemic of Covid-19. A survey has been done to achieve the objectives of this paper. It is found that online banking playing an important role in the Covid 19 period to protect the people. People felt completely safe from the COVID 19 virus in the online payment of bills and recharge of prepaid mobiles and dish T.V.